Research on Hybrid Heating System in Cold Oilfield Regions - Meng Xu; Zhiyang Xu; Xinxin Wei; Gaoxiang Zhang; Changyu Liu (Clean Technologies, 2024)
Efficient and clean treatment of wastewater and energy recovery and utilization are important links to realize low-carbon development of oilfields. Therefore, this paper innovatively proposes a multi-energy complementary co-production heating system which fully and efficiently utilizes solar energy resources, oilfield waste heat resources, and biomass resources. At the same time, a typical dormitory building in the oil region was selected as the research object, the system equipment selection was calculated according to the relevant design specifications. On this basis, the simulation system model is established, and the evaluation index and operation control strategy suitable for the system are proposed. The energy utilization rate of the system and the economic, energy-saving, and environmental benefits of the system are simulated. The results show that, under the simulated conditions of two typical days and a heating season, the main heat load of the system is borne by the sewage source heat pump, the energy efficiency is relatively low in the cold period, and the energy-saving characteristics are not obvious. With the increase in heating temperature and anaerobic reactor volume, the energy consumption of the system also increases, and the energy efficiency ratio of each subsystem and the comprehensive energy efficiency ratio of the system gradually decrease. In addition, although the initial investment in cogeneration heating systems is high, the operating costs and environmental benefits are huge. Under the condition of maintaining 35 °C, the anaerobic reactor in the system can reduce carbon emissions by 12.15 t per year, reduce sulfur dioxide emissions by 98.4 kg, reduce dust emissions by 49.2 kg, and treat up to 2700 t of sewage per year, which has broad application prospects.